Artificial Intelligence in Oral and Maxillofacial Radiology- New Trend in Image Assessment - Ghazizadeh Ahsaie, Mitra (Journal of Dental School, 2023)
I am Writing to share my professional opinion regarding the application of Artificial intelligence (AI) in oral and maxillofacial radiology. Intelligent systems (i.e., AI), are machines able to mimic the cognitive functions of humans to perform tasks of problem-solving and learning. AI is becoming important in radiology due to its ability to detect abnormalities in radiographic images. These systems have reduced radiologists’ workload by rapidly recording and presenting data, and thereby monitoring the treatment response with a reduced risk of cognitive bias. Some of the most common applications of AI in dentomaxillofacial radiology are: tooth and implant classification and identification, 3D cephalometric landmark detection, lesion detection (periapical, jaws, and bone), and osteoporosis detection. Therefore, these intelligent systems have an important role to play and could be used by dentists as an adjunct to other imaging modalities in making appropriate diagnoses and treatment plans. However, AI potentials and pitfalls should be thoroughly assessed especially in critical cases, and it seems even when achieving high success rates, radiologists’ supervision is necessary in most cases.